Type 3 Fimbrial Shaft (MrkA) of Klebsiella pneumoniae, but Not the Fimbrial Adhesin (MrkD), Facilitates Biofilm Formation - Langstraat, Jennifer (American Society for Microbiology, 2001)
Isolates of Klebsiella pneumoniae are responsible for opportunistic infections, particularly of the urinary tract and respiratory tract, in humans. These bacteria express type 3 fimbriae that have been implicated in binding to eucaryotic cells and matrix proteins. The type 3 fimbriae mediate binding to target tissue using the MrkD adhesin that is associated with the fimbrial shaft comprised of the MrkA protein. The formation of biofilms in vitro by strains of K. pneumoniae was shown to be affected by the production of fimbriae on the bacterial surface. However, a functional MrkD adhesin was not necessary for efficient biofilm formation. Nonfimbriate strains were impaired in their ability to form biofilms. Using isogenic fimbriate and nonfimbriate strains of K. pneumoniae expressing green fluorescent protein it was possible to demonstrate that the presence of type 3 fimbriae facilitated the formation of dense biofilms in a continuous-flowthrough chamber. Transformation of nonfimbriate mutants with a plasmid possessing an intact mrk gene cluster restored the fimbrial phenotype and the rapid ability to form biofilms.